2015
DOI: 10.1016/j.freeradbiomed.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cytochrome P4501A2 in mice leads to increased susceptibility to hyperoxic lung injury

Abstract: Hyperoxia contributes to acute lung injury (ALI) in diseases such as acute respiratory distress syndrome (ARDS). Cytochrome P450 (CYP)1A enzymes have been implicated in hyperoxic lung injury, but the mechanistic role(s) of CYP1A2 in pulmonary injury is not known. We hypothesized that mice lacking the gene for Cyp1a2 (which is predominantly expressed in the liver) will be more sensitive to lung injury and inflammation mediated by hyperoxia, and that CYP1A2 will play a protective role by attenuating lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…The protective effects of CYP1A enzymes against hyperoxia-induced lung injury in rodents have been extensively documented [26, 4143]. In addition, NQO1 has been shown to protect cells and tissues against oxidant injury induced by various toxic chemicals [44] and oxygen [45].…”
Section: Resultsmentioning
confidence: 99%
“…The protective effects of CYP1A enzymes against hyperoxia-induced lung injury in rodents have been extensively documented [26, 4143]. In addition, NQO1 has been shown to protect cells and tissues against oxidant injury induced by various toxic chemicals [44] and oxygen [45].…”
Section: Resultsmentioning
confidence: 99%
“…Also, circulating F 2 -isoprostanes are considered to play a role in inflammatory lung diseases by various receptor-triggered pathways (for review, see [91]). In a recent work by Wang and coworkers [92], it was shown that knocking out Cyp1a2, primarily expressed in the liver, also increased susceptibility for hyperoxic lung injury. This was assessed by the ratio weight lung /weight body and histology, pulmonary neutrophil infiltration, cytokine expression, lipid peroxidation, and F 2 -isoprostane levels in liver and lung [92].…”
Section: Protective Function Of Ahr In Hyperoxic Lung Injurymentioning
confidence: 99%
“…In a recent work by Wang and coworkers [92], it was shown that knocking out Cyp1a2, primarily expressed in the liver, also increased susceptibility for hyperoxic lung injury. This was assessed by the ratio weight lung /weight body and histology, pulmonary neutrophil infiltration, cytokine expression, lipid peroxidation, and F 2 -isoprostane levels in liver and lung [92]. The authors finally provide evidence for CYP1A2-mediated metabolism of PGF 2 - α in vitro supporting the idea that CYP1A1 and CYP1A2 protect against oxidative stress by decreasing the amount of lung- or liver-derived circulating F 2 -isoprostanes.…”
Section: Protective Function Of Ahr In Hyperoxic Lung Injurymentioning
confidence: 99%
“…Cytochrome P450 metabolism of Xenobiotics pathway contains 7 intersection genes that include Cyp1a1, Cyp1a2 and Gstm1, which might be the most related pathway to hepatotoxicity induced by psoralen and isopsoralen. CYP450s, as the primary enzymes for phase I drug metabolism, involved in the metabolism of various exogenous and endogenous compounds . Another important pathway impacted by psoralen and isopsoralen was Chemical Carcinogenesis because Cyp1a1, Cyp1a2, Ephx1, Gstm1 and Aldh3a1 all involved in this.…”
Section: Discussionmentioning
confidence: 99%